Analisis Kinerja Algoritma SVM dan Naïve Bayes untuk Klasifikasi Sentimen Program Makan Gratis - Iranda, Muhammad; Huda, Nurul (STMIK Banjarbaru, 2025)
The development of social media facilitates the massive dissemination of public opinion, including towards the government’s free meal program. The high volume of comments makes manual analysis inefficient, thus requiring technological approaches such as sentiment analysis for automatic opinion classification. This study focuses on comparing the performance of the SVM (Support Vector Machine) and Naïve Bayes algorithms in classifying public sentiment collected from X social media data. The research method includes data crawling, preprocessing with Natural Language Processing (NLP), and classification using both algorithms. Testing results on an imbalanced dataset show that SVM is the best model with 96% accuracy and an F1-score of 0.48 for the minority (negative) class, significantly outperforming Naïve Bayes variants which tend to predict the majority class. The findings demonstrate that the SVM algorithm has higher reliability in sentiment classification on datasets with imbalanced class distribution.Keywords: Sentiment Analysis; Support Vector Machines; Naive Bayes; Free Lunch Program; Text Classification AbstrakPerkembangan media sosial memfasilitasi penyampaian opini publik secara masif, termasuk terhadap program makan gratis pemerintah. Volume komentar yang tinggi menjadikan analisis manual tidak efisien, sehingga memerlukan pendekatan teknologi seperti analisis sentimen untuk klasifikasi opini otomatis. Penelitian ini berfokus pada perbandingan performa algoritma SVM (Support Vector Machine) dan Naïve Bayes dalam mengklasifikasikan sentimen masyarakat yang diambil dari data media sosial X. Metode penelitian mencakup pengumpulan data crawling, pra-pemrosesan dengan Natural Language Processing (NLP), hingga klasifikasi menggunakan kedua algoritma. Hasil pengujian pada dataset yang tidak seimbang menunjukkan bahwa SVM merupakan model terbaik dengan akurasi 96% dan nilai F1-score 0.48 pada kelas minoritas (negatif), secara signifikan mengungguli varian Algoritma Naïve Bayes sering kali lebih condong memprediksi pada kelas mayoritas. Hasil penelitian ini membuktikan bahwa algoritma SVM memiliki keandalan lebih tinggi dalam klasifikasi sentimen pada dataset dengan distribusi kelas yang tidak seimbang.